Empowerment for sustainable development : toward operational strategies - Titi, Vangile ed. (Zed Books Ltd. LondonGB, 1995)
Provides an overview of concepts, empowerment methods and challenges. Highlights the potential for change, including legal and institutional reforms inherent in the concept and principles of sustainable development. Examines education as an empowermenet tool in the sustainable development process. Looks at building upon empowerment strategies that have been tried and tested to support sustainable development goals. Highlights some of the underlying principles, including accountability and democracy, which must inform operational strategy of empowerment for sustainable development.